ELECTRONIC HEALTH RECORDS AND HEALTHCARE QUALITY IN NIGERIA: A NARRATIVE REVIEW OF BENEFITS, CHALLENGES, AND POLICY IMPLICATIONS - Chibuzo Onyema, Matthias (African Journal of Social and Behavioural Sciences, 2026)
Electronic Health Records (EHRs) have become central to contemporary healthcare reform because they improve the storage, retrieval, sharing, and use of patient information. In Nigeria, where healthcare delivery is frequently constrained by weak infrastructure, fragmented records, limited workforce capacity, and uneven data quality, EHRs offer significant opportunities for improving clinical decision-making, patient safety, care coordination, and health system planning. This paper adopts a narrative review method to examine the role of EHRs in improving healthcare quality in Nigeria. Although relevant scholarly literature and policy-oriented sources on EHR adoption, digital health, health information systems, and healthcare quality were reviewed and thematically synthesized. The review shows that EHRs can enhance healthcare quality by improving access to patient records, reducing documentation errors, supporting continuity of care, strengthening health data management, and enabling evidence-informed policy decisions. However, the effective adoption of EHRs in Nigeria remains limited by inadequate digital infrastructure, high implementation costs, poor interoperability, insufficient training, data security concerns, and resistance to technological change among healthcare workers. Using the socio- technical approach as its theoretical lens, the paper argues that successful EHR implementation requires more than technological investment; it also demands attention to users, institutions, workflows, policy frameworks, and organizational culture. The paper concludes that EHRs can significantly improve healthcare quality in Nigeria if implementation is supported by sustainable funding, workforce training, interoperability standards, cybersecurity safeguards, and context- sensitive digital health policies.